Tectono-thermal evolution of a long-lived segment of the East African Rift System: Thermochronological insights from the North Lokichar Basin, Turkana, Kenya - Samuel C. Boone (2018)
© 2018 Elsevier B.V. The Turkana Depression is a structurally complex and long-lived segment of the East African Rift System (EARS), with associated magmatism and strain nucleating there in the late Paleogene. The anomalously wide, ~N-S rift zone defines the topographic lowlands separating the Ethiopian and East African Domes. The atypical architecture and morphology of the Turkana Depression has often been attributed to the influence of an oblique, pre-existing lithospheric heterogeneity speculated to result from earlier Cretaceous-early Paleogene Anza-South Sudan rifting. However, this hypothesized period of earlier rifting is poorly constrained due to the obscuring effects of extensive Cenozoic rifting and volcanism. Similarly, the extent and timing of basin formation during the initial stages of EARS extension in Turkana is not well understood. Seismic reflection studies in Turkana have revealed the presence of older, possibly late Paleogene sub-basins, predating the Neogene onset of major faulting elsewhere in the EARS. One example, the Lothidok Basin, has previously been imaged beneath the late Miocene-Pliocene North Lokichar Basin. Its age, however, is unconstrained due to a lack of well controls, geochronological constraints and outcrop of its basal unit. Here, we present a multiple low-temperature thermochronometer [apatite fission track, apatite (U-Th-Sm)/He and zircon (U-Th)/He] study performed on Precambrian basement samples from the western margin of the overlying North Lokichar Basin. Thermal history modelling reveals a polyphase Late Cretaceous-Recent tectono-thermal evolution providing new insights into pre-EARS tectonism in Turkana and subsequent, late Paleogene ~E-W extension. Pronounced Late Cretaceous-Paleogene denudational cooling challenges the theorized linkage of the Anza-South Sudan Rifts in Turkana, perhaps suggesting later Paleogene tectonism played a more critical role in modifying the lithosphere. Subsequent Oligocene-early Miocene reheating is interpreted as resulting from burial beneath ~200–800 m of overburden, accordant with the proposed formation of the Lothidok Basin and/or coeval emplacement of thick lava flows in the region.